Hardcore Differentials!

Calculus Level 4

If the general solution of the differential equation,

[ y + x x y ( x + y ) ] d x + [ y x y ( x + y ) x ] d y = 0 [y+x\sqrt { xy } (x+y)]dx\quad +\quad [y\sqrt { xy } (x+y)-x]dy\quad =\quad 0

is if the form ,

x r + y s t + u tan 1 x y + C = 0 \frac { { x }^{ r }+{ y }^{ s } }{ t } +u\tan ^{ -1 }{ { \sqrt { \frac { x }{ y } } } } +\quad C\quad =\quad 0

where C is a constant , t , u 1 t,u\neq 1

and r , s , t , u > 0 r,s,t,u>0 then find the value of r+s+t+u.


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Emil Joseph
Jan 11, 2015

The given equation can be expanded as, ( y d x x d y ) + x y ( x + y ) [ x d x + y d y ] = 0 (ydx-xdy)\quad +\quad \sqrt { xy } (x+y)[xdx\quad +ydy]\quad =0

on dividing the equation by y 2 { y }^{ 2 }

y d x x d y y 2 + x y y ( x + y ) y [ x d x + y d y ] = 0 \frac { ydx-xdy }{ { y }^{ 2 } } +\frac { \sqrt { xy } }{ y } \frac { (x+y) }{ y } [xdx+ydy]\quad =\quad 0

we can observe that the first term is actually , d ( x y ) d(\frac { x }{ y } )

d ( x y ) + x y ( x y + 1 ) [ x d x + y d y ] = 0 \Rightarrow \quad d(\frac { x }{ y } )+\sqrt { \frac { x }{ y } } (\frac { x }{ y } +1)[xdx+ydy]\quad =\quad 0

d ( x y ) + x y ( ( x y ) 2 + 1 ) [ x d x + y d y ] = 0 \Rightarrow \quad d(\frac { x }{ y } )+\sqrt { \frac { x }{ y } } ({ (\sqrt { \frac { x }{ y } } ) }^{ 2 }+1)[xdx+ydy]\quad =\quad 0

d ( x y ) = x y ( ( x y ) 2 + 1 ) [ x d x + y d y ] \Rightarrow \quad d(\frac { x }{ y } )\quad \quad \quad =\quad -\sqrt { \frac { x }{ y } } ({ (\sqrt { \frac { x }{ y } } ) }^{ 2 }+1)[xdx+ydy]

d ( x y ) x y ( ( x y ) 2 + 1 ) = { x d x + y d y } \Rightarrow \quad \int { \frac { d(\frac { x }{ y } ) }{ \sqrt { \frac { x }{ y } } (({ \sqrt { \frac { x }{ y } } ) }^{ 2 }+1) } } =\quad -\quad \{ \int { xdx } +\int { ydy\} }

on integrating both sides,

2 tan 1 x y + C = { x 2 + y 2 2 } \Rightarrow 2\tan ^{ -1 }{ \sqrt { \frac { x }{ y } } } \quad +\quad C\quad =\quad -\quad \{ \frac { { x }^{ 2 }+{ y }^{ 2 } }{ 2 } \} \quad

x 2 + y 2 2 + 2 tan 1 x y + C = 0 \Rightarrow \quad \frac { { x }^{ 2 }+{ y }^{ 2 } }{ 2 } \quad +\quad 2\tan ^{ -1 }{ \sqrt { \frac { x }{ y } } } \quad +\quad C\quad =\quad 0

hence r+s+t+u = 8 \boxed { 8 }

Hope you guys understood it :)

If you got an easier solution , don't hesitate to put it up!

or you can differentiate the equation it is comparably easy

Rishabh Deep Singh - 5 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...